Pengaruh Penggunaan Media Sosial Whatsapp Dan Motivasi Belajar Terhadap Keaktifan Siswa Pada Mata Pelajaran Ekonomi Kelas X Di SMA Negeri 5 Padang - Caterina Lo; Reni Respita; Henimar (Kilau Publishing, 2025)
The purpose of this study is to analyze the effect of WhatsApp social media use and learning motivation on students’ activeness in Economics for Grade X at SMA Negeri 5 Padang. This research employed a quantitative design with a population of all Grade X students. The sample consisted of 78 students selected through simple random sampling. Data were collected using questionnaires and analyzed using multiple linear regression, along with t-tests and an F-test. The results indicate that WhatsApp use has a positive and significant effect on students’ activeness (b = 0.505; t = 3.436; p = 0.001), learning motivation also has a positive and significant effect (b = 0.543; t = 3.512; p < 0.001), and both variables simultaneously have a significant effect (F = 12.913; p < 0.001), with an explained variance contribution of R² = 0.656. It is recommended that WhatsApp be utilized as a learning medium—such as class groups, sharing learning materials, and structured discussions—supported by usage rules to prevent distractions, and that motivation-strengthening strategies (learning goals, feedback, and participation reinforcement) be implemented to enhance student activeness. Future studies should include additional variables beyond the current model and expand the sample and school context.